(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The phrase "geographic information systems" describes computer-aided methods for gathering, storing, retrieving, analysing, and presenting geographic data. The increased use and complexity of these systems have resulted in a renewed interest in them among academics, and this has led to the growth and activity of a research community. even when formalised semantics, categorizations, terminologies, and standard data formats are frequently lacking. Published work exhibits a remarkable degree of interdisciplinary cooperation. This paper examines published research on geographic information systems, with a particular emphasis on GIS data structures, and concludes that graduates from future generations will be far more qualified to meet the demands of this emerging technology. A brief explanation of the arrangement and structure of the information is included, along with a discussion of many methods for representing geographic data and information from the real world in geographic information systems. Second, several perspectives on the arrangement of data are looked at. These perspectives encompass the many types of spatial relationships that geographic information systems handle in addition to the underlying information organisation structure found inside GISs. In summary, the concept of data is examined, along with the role that databases play in relation to geographic information systems. This includes a discussion of the many methods that may be used to represent connections, processes, and data from the actual world into databases.